El cumplimiento del derecho a la jubilación en los trabajadores del GAD Municipal del cantón Guano en el año 2021. - Velasteguí Estrada, Yesenia Belén (2022)
The present research project with the title "The fulfillment of the right to retirement in the workers of the Municipal GAD of the Guano canton", has the purpose of carrying out a study of the full fulfillment of the right to retirement of the workers of the Municipal GAD of the Guano canton, given that there are a number of cases of workers who, fulfilling the requirements to avail themselves of this benefit, have not done so to date. The Constitution and jurisprudence constitute and protect the retirement pension as a social right that must be guaranteed —as much as possible— by the State, in order to satisfy basic individual needs. From here, it is considered necessary that, within the analysis of the reasonableness of retirement pensions, it is taken into account that: It is an autonomous acquired right and of equal gradation to others, which requires a minimum realization. Starting from this base, it is important to analyze the right to retirement in the workers of the Municipal GAD of the Guano canton, since, in the first instance, it is violating the constitutional rights of a vulnerable group and at the same time it is an obstacle to the development of good to live. Indeed, a qualitative and quantitative research is carried out because it is based on the collection of reference documents to the subject with the tension of having the information supported and also the situation of the population is known through the survey. Keywords: Retirement, Labor Law, Infringement..